In vivo imaging of alphaherpesvirus infection reveals synchronized activity dependent on axonal sorting of viral proteins - Granstedt, Andrea E. (National Academy of Sciences, 2013)
A clinical hallmark of human alphaherpesvirus infections is peripheral pain or itching. Pseudorabies virus (PRV), a broad host range alphaherpesvirus, causes violent pruritus in many different animals, but the mechanism is unknown. Previous in vitro studies have shown that infected, cultured peripheral nervous system (PNS) neurons exhibited aberrant electrical activity after PRV infection due to the action of viral membrane fusion proteins, yet it is unclear if such activity occurs in infected PNS ganglia in living animals and if it correlates with disease symptoms. Using two-photon microscopy, we imaged autonomic ganglia in living mice infected with PRV strains expressing GCaMP3, a genetically encoded calcium indicator, and used the changes in calcium flux to monitor the activity of many neurons simultaneously with single-cell resolution. Infection with virulent PRV caused these PNS neurons to fire synchronously and cyclically in highly correlated patterns among infected neurons. This activity persisted even when we severed the presynaptic axons, showing that infection-induced firing is independent of input from presynaptic brainstem neurons. This activity was not observed after infections with an attenuated PRV recombinant used for circuit tracing or with PRV mutants lacking either viral glycoprotein B, required for membrane fusion, or viral membrane protein Us9, required for sorting virions and viral glycoproteins into axons. We propose that the viral fusion proteins produced by virulent PRV infection induce electrical coupling in unmyelinated axons in vivo. This action would then give rise to the synchronous and cyclical activity in the ganglia and contribute to the characteristic peripheral neuropathy.